Dancing on violent ground : utopia as dispossession in Euro-American theater dance - Stanger, Arabella (Performance works., 2021)
"Developing a new theory of choreographic space, the author shows how embodied forms of hope promised in ballet and progressive dance modernisms conceal and depend on spatial operations of imperial, colonial, and racial subjection"--